1990
DOI: 10.1121/1.399442
|View full text |Cite
|
Sign up to set email alerts
|

The calculation of acoustic fields in solids for transient normal surface force sources of arbitrary geometry and apodization

Abstract: Methods used to calculate the radiated acoustic field of transient normal surface force sources applied to elastic solids have previously included significant approximations or have constrained the surface force distribution in practically restrictive ways. In this paper, a theoretically exact, quantitative, numerical solution to the problem is described. The only constraint on the applied suface force in this solution is that it is cophased. Nevertheless, by efficient numerical construction, the computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…If noise in the original waveforms is uniform then this apodization maximizes the signal to noise ratio (SNR) at each point in image. As a result, the intensity of the image, I(r), is given by [9], [10]:…”
Section: The Full Matrix Capture and The Total Focusing Methodsmentioning
confidence: 99%
“…If noise in the original waveforms is uniform then this apodization maximizes the signal to noise ratio (SNR) at each point in image. As a result, the intensity of the image, I(r), is given by [9], [10]:…”
Section: The Full Matrix Capture and The Total Focusing Methodsmentioning
confidence: 99%
“…While some condensed volumes on the matter in general have been compiled [12,13,14,15,16,17,18], most of the relevant research is mainly scattered in time and throughout literature. One can find, for example, expositions on pressure-induced [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35] as well as thermal-expansion-induced [26,27,28,29,30,31,32,33,35,36,37,38,39,40,41,42,43,44] ultrasound propagation in a half-space [21,22,23,24,25,26,27,...…”
Section: Introductionmentioning
confidence: 99%
“…Above 60°, another maximum appears that is no Ionger centered on the steering angle, and is possibly associated with increased plate wave generation and leakage into the specimen. Previous work (3] has shown that the element directivities can be associated with elastic-wave sources having a Gaussian force profile, which are active on the surface of the specimen. The effective width of these sources is larger than the element itself, due partly to the Gaussian electric field on the bottom surface of the Iithium niobate, and partly to the high divergence ofwaves propagating within the plate from the top and bottom surfaces.…”
Section: Array Performancementioning
confidence: 99%